Prevalence and Associated Factors of Restless Leg Syndrome (RLS) in Pakistani Women during Pregnancy - Sania, Shagufta Parveen, Uzma Zia, Fouzia Unar, Masood Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the prevalence and associated factors of restless leg syndrome (RLS) in Pakistani women during pregnancy. Study design: Cross-sectional study Place and duration of study: Department of Obstetrics & Gynaecology, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat from 1st January 2021 to 31st December 2021. Methodology: One hundred and twenty patients information were collected by interviewing them to assess and document data related to factors associated with their RLS. Four criteria were used for diagnosis RLS based on related literature reference. The severity condition was assessed with the ten items with rating as five points starting from none to v. severe. Epworth Sleepiness Scale was used to analyses day time sleep while quality of sleep was analyzed by using Pittsburgh-Sleep Quality-Index. Results: Obesity was presented as highest comorbidity with 56.6% of prevalence in RLS pregnant women followed by hypertension. Within the RLS pregnant women it was observed that majority were taking tea with a prevalence of 61% while 36% were consuming coffee as well. The univariant analysis showed that third trimester, depression and parity were significant factors associated with the RLS during pregnancy. Conclusion: Restless leg syndrome is associated with factors as third trimester, poor quality of sleep, depression and parity while depression and hypertension were also seemed to carry a substantial role in development of RLS. Keywords: Third trimester, inactivity, pregnancy, prevalence, serotonin